Visual Perturbation to Enhance Return to Sport Rehabilitation after Anterior Cruciate Ligament Injury: A Clinical Commentary - Timothy R Wohl (North American Sports Medicine Institute, 2021)
Anterior cruciate ligament (ACL) tears are common traumatic knee injuries causing joint instability, quadriceps muscle weakness and impaired motor coordination. The neuromuscular consequences of injury are not limited to the joint and surrounding musculature, but may modulate central nervous system reorganization. Neuroimaging data suggest patients with ACL injuries may require greater levels of visual-motor and neurocognitive processing activity to sustain lower limb control relative to healthy matched counterparts. Therapy currently fails to adequately address these nuanced consequences of ACL injury, which likely contributes to impaired neuromuscular control when visually or cognitively challenged and high rates of re-injury. This gap in rehabilitation may be filled by visual perturbation training, which may reweight sensory neural processing toward proprioception and reduce the dependency on vision to perform lower extremity motor tasks and/or increase visuomotor processing efficiency. This clinical commentary details a novel approach to supplement the current standard of care for ACL injury by incorporating stroboscopic glasses with key motor learning principles customized to target visual and cognitive dependence for motor control after ACL injury.